Surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material and preparation method thereof

By plating nickel plating on the surface of PBO short -cut fiber and combining discharge -backed plasma sintering and high temperature annealing process, the problem of limited intensity between PBO fiber and aluminum -based interface interfaces significantly improves the comprehensive mechanical performance of aluminum -based composite materials.

CN119372566AActive Publication Date: 2025-01-28SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411560046.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In the prior art, the interfacial bonding strength between PBO fiber and aluminum matrix is ​​limited, which limits the comprehensive mechanical properties of aluminum-based composite materials.

Method used

Through ultrasonic scattered and chemical nickel plating processes, nickel plating nickel plating on the PBO short -cut fiber surface, combined with discharge plasma sintering and high temperature annealing process to prepare surface nickel -plated PBO short -cut fibers to enhance aluminum -based composite materials.

Benefits of technology

The interface binding force between the fiber and the aluminum -based body is significantly improved, and the density, stretching yield strength, tensile strength and curved strength of the composite materials are improved, and the plastic deformation ability is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material and a preparation method thereof, and belongs to the technical field of metal-based composite materials. The surface nickel-plated PBO fiber reinforced aluminum-based composite material is prepared through fiber ultrasonic dispersion, fiber coarsening, fiber surface nickel plating, ball milling and powder mixing, spark plasma sintering and subsequent high-temperature annealing. The surface of the PBO chopped fiber is coated with the metal nickel layer, the element diffusion and reaction process between the PBO chopped fiber and the aluminum matrix is effectively promoted, a NiAl intermetallic compound reaction layer with good plasticity and toughness is generated, the interface bonding strength of the fiber / matrix is improved, and therefore the comprehensive mechanical property of the composite material is further improved. The compactness of the surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material reaches 99.0% or above, the maximum tensile yield strength can reach 270 MPa, the maximum tensile strength can reach 320 MPa, the maximum bending strength can reach 435 MPa, the maximum percentage elongation after fracture can reach 14.0%, and the surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material has good comprehensive mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal-based composite materials, and particularly relates to a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] Aluminum-based composite materials are composite materials with aluminum or aluminum alloy as the matrix and continuous long fibers, short fibers, whiskers and particles as the reinforcement phase. They have excellent comprehensive properties such as high specific strength, corrosion resistance, and low expansion coefficient, and are relatively low in cost. They have broad application prospects in the aviation, aerospace, automotive, armor protection and other industrial fields. The research and development and application of aluminum-based composite materials began in the 1950s. The commonly used reinforcement materials are mainly silicon carbide fibers, particles, nanocarbon (graphene, carbon nanotubes) and carbon fibers. Among them, carbon fibers have high strength and modulus, and have a significant strengthening effect on the matrix. However, due to the interfacial reaction between the aluminum matrix and the carbon fibers to generate Al4C3 brittle phase, it has an adverse effect on the comprehensive performance of the composite material. At present, carbon fiber reinforced aluminum-based composite materials are still in the research stage.

[0003] Compared with carbon fiber and silicon carbide fiber, PBO fiber (poly(p-phenylene benzobisoxazole) fiber) has higher strength and modulus, its tensile strength reaches 5.8GPa, and it has better plasticity (elongation after fracture: 3.5%), making it a more ideal reinforcement material. At the same time, PBO fiber has excellent impact resistance, high temperature resistance, friction resistance and dimensional stability, and is called the "super fiber of the 21st century". Therefore, compared with carbon fiber, PBO fiber can more effectively improve the comprehensive mechanical properties of aluminum-based composites. However, PBO fiber has a smooth surface, no polar group, and will not diffuse or react with the aluminum matrix to generate interface products during the sintering process, resulting in limited interface bonding strength between it and the aluminum matrix, which is not conducive to further improvement of the comprehensive mechanical properties of the composite material. Surface nickel plating refers to the use of chemical plating or electroplating process to coat a layer of metal nickel on the surface of the fiber or the like, promoting the formation of an interface phase between the fiber surface and the metal matrix by diffusion or reaction, so as to improve the interface bonding strength between the two. However, at present, research on surface nickel-plated PBO fiber reinforced aluminum-based composites has not yet been carried out. On this basis, it is unpredictable whether nickel-plated PBO fibers can further improve the comprehensive mechanical properties of aluminum-based composites and how to prepare nickel-plated PBO fiber-reinforced aluminum-based composites. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material and a preparation method thereof. First, an ultrasonic dispersion device is used to disperse the PBO chopped fibers and roughen the fibers, and then a layer of metal nickel is coated on the surface of the PBO chopped fibers by a chemical nickel plating process, and then the surface nickel-plated PBO chopped fibers and aluminum powder are placed in a ball mill according to a predetermined ratio, and ball milling and mixing treatment is carried out by a three-dimensional planetary vibration ball mill to fully mix and obtain a mixed material; then the mixed material is placed in a cemented carbide mold, and placed in a spark plasma sintering furnace (SPS), and sintered under high temperature and high pressure conditions to obtain a composite material blank, and finally the composite material blank is placed in a vacuum atmosphere sintering furnace for high temperature annealing to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material, thereby achieving the purpose of the present invention.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material, the method comprising the following steps: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) in concentrated sulfuric acid for roughening treatment, wherein the concentration of the concentrated sulfuric acid is 60-90% and the immersion time is 10-40 seconds. After immersion, the fibers are rinsed with deionized water to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.02~0.08mol / L, the concentration of sodium citrate is 0.01~0.10mol / L, the concentration of sodium hypophosphite is 0.05~0.20mol / L, the concentration of sodium pyrophosphate is 0.10~0.30mol / L, the pH regulator is NaOH, KOH or ammonia water, and the pH value of the nickel plating solution is 9~13; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of sodium hypophosphite being 10-45 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency being 10-20 kHz, the nickel plating temperature being 50-90° C., the nickel plating reaction time being 60-150 min, and after the nickel plating is completed, rinsing the fibers with deionized water for 7-10 times and drying at 70-120° C. to obtain PBO chopped fibers with surface nickel plating; (5) Mixing the nickel-plated PBO chopped fibers and aluminum powder into a ball mill, wherein the mass fraction of the nickel-plated PBO chopped fibers is 2-10 wt%, and adding alumina ball milling balls, wherein the ball-to-material ratio is 2-8:1; (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment, the ball milling speed is 100-500 r / min, and the ball milling time is 2-8 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) placing the mixed material into a cemented carbide mold and placing it in a spark plasma sintering (SPS) furnace for sintering treatment, the sintering temperature is 450-600°C, the sintering pressure is 100-300 MPa, and the heat preservation and pressure holding time is 10-45 min. After the sintering is completed, demolding is performed to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite body; (8) The surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material blank is placed in a vacuum atmosphere sintering furnace for high-temperature annealing treatment. The annealing temperature is 300-500°C and the annealing insulation time is 1-4 hours. After the annealing is completed, it is cooled to room temperature with the furnace to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material.

[0006] Preferably, in step (2), the length of the PBO chopped fibers is 1-6 mm, the concentration of concentrated sulfuric acid used for the roughening treatment is 70-80%, and the immersion time is 20-40 s; Preferably, in step (3), the nickel plating solution contains Ni 2+ The concentration of is 0.03~0.06mol / L, the concentration of sodium citrate is 0.02~0.05mol / L, the concentration of sodium hypophosphite is 0.10~0.16mol / L, the concentration of sodium pyrophosphate is 0.15~0.25mol / L, and the pH value of the nickel plating solution is 10~12; Preferably, in step (4), the concentration of sodium hypophosphite is 15-30 g / L, the nickel plating temperature is 60-80° C., and the nickel plating reaction time is 80-120 min; Preferably, in step (5), the particle size of the aluminum powder is 20-200 μm, the mass fraction of the nickel-plated PBO chopped fibers is 3-7 wt %, and the pellet-to-material ratio is 3-6:1; Preferably, in step (6), the ball milling speed is 200-400 r / min, and the ball milling time is 3-5 h; Preferably, in step (7), the spark plasma sintering temperature is 475-575°C, the sintering pressure is 150-250 MPa, and the heat and pressure holding time is 15-30 min; Preferably, in step (8), the high temperature annealing temperature is 350-450° C., and the annealing holding time is 2-3 h.

[0007] A surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the method.

[0008] Beneficial effects of the present invention: (1) The present invention relates to a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material and a preparation method thereof, wherein the composite material preparation process comprises ultrasonic dispersion of PBO chopped fibers, nickel plating of fiber surfaces, ball milling and powder mixing, spark plasma sintering, and subsequent high-temperature annealing. Before the nickel plating treatment, the PBO chopped fibers are roughened to make their surfaces rough, which is beneficial to increase the bonding force between the fibers and the nickel plating layer, thereby facilitating the subsequent nickel plating treatment.

[0009] (2) The nickel plating reaction temperature and time have an important influence on the nickel plating effect and the comprehensive mechanical properties of the composite material: when the nickel plating reaction temperature is too low and the reaction time is too short, the degree of chemical reaction is low, resulting in a thin, unevenly distributed and non-dense nickel plating layer on the PBO surface, which leads to limited interfacial bonding strength between the fiber and the aluminum matrix; and when the nickel plating reaction time is too long, on the one hand, the nickel plating layer will be too thick, and uneven plating thickness will easily occur, resulting in reduced interfacial bonding strength of the composite material; on the other hand, too long nickel plating time will also lead to low nickel plating efficiency.

[0010] (3) The fiber reinforcement content in the composite material is 1wt%~10wt%. When the reinforcement content is lower than 1wt%, its reinforcing effect on the matrix is ​​limited. When the reinforcement content is higher than 10wt%, the fiber is prone to agglomeration during the ball milling process, resulting in a reduction in its reinforcing effect. At the same time, the sintering method used is the spark plasma sintering process. Different from conventional hot pressing sintering, the spark plasma sintering process has a fast heating rate, which can greatly shorten the sintering time and improve the sintering efficiency. At the same time, the low temperature and high pressure sintering mode can effectively prevent the damage of the PBO chopped fibers and the melting of the aluminum matrix caused by the excessively high sintering temperature. (4) During the spark plasma sintering process, the nickel-plated layer on the surface of the PBO fiber and the aluminum matrix can undergo atomic diffusion and react to form a NiAl intermetallic compound reaction layer with good plasticity and toughness, thereby effectively improving the interfacial bonding force between the fiber reinforcement and the aluminum matrix, and more effectively exerting the role of the fiber reinforcement, thereby further improving the comprehensive mechanical properties of the aluminum-based composite material; (5) The present invention relates to a PBO chopped fiber reinforced aluminum-based composite material and a preparation method thereof. The PBO chopped fibers have a good strengthening effect on the aluminum matrix. The density of the PBO chopped fiber reinforced aluminum-based composite material is above 99.0%, the maximum tensile yield strength can reach 270 MPa (pure aluminum yield strength < 70 MPa), the maximum tensile strength can reach 320 MPa (pure aluminum tensile strength < 90 MPa), and the maximum bending strength can reach 435 MPa (pure aluminum bending strength < 120 MPa). At the same time, the PBO chopped fiber reinforced aluminum-based composite material has good plastic deformation ability, and its maximum elongation after fracture can reach 14.0%, and has good comprehensive mechanical properties. DETAILED DESCRIPTION

[0011] The technical solution of the present invention is further described in detail below in conjunction with embodiments. Obviously, the embodiments described here are only used to explain the present invention, but the present invention is not limited to these embodiments.

[0012] In the following embodiments: (1) Density testing equipment: JA2003 electronic balance.

[0013] (2) Tensile test equipment: an electronic universal material testing machine model INSTRON5985 (Instron, USA) was used.

[0014] (3) Yield strength, tensile strength and elongation are measured according to GB / T228-2002 from the tensile stress-strain curve obtained from the tensile test.

[0015] (4) The bending strength was measured using an INSTRON5985 electronic universal materials testing machine (Instron, USA) in accordance with GB / T232-2010 “Methods for bending tests of metallic materials”.

[0016] Example 1 In this embodiment, a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the following method: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) into concentrated sulfuric acid for roughening treatment, wherein the length of the PBO chopped fibers is 1 mm, the concentration of the concentrated sulfuric acid is 60%, and the immersion time is 40 seconds to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+The concentration of is 0.02mol / L, the concentration of sodium citrate is 0.01mol / L, the concentration of sodium hypophosphite is 0.20mol / L, the concentration of sodium pyrophosphate is 0.30mol / L, the pH regulator is NaOH, and the pH value of the nickel plating solution is 9; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 10 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 50°C, the nickel plating reaction time is 60 min, and after the nickel plating is completed, the fibers are rinsed with deionized water 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; (5) PBO chopped fibers with nickel coating and aluminum powder were mixed and placed in a ball mill, wherein the aluminum powder had a particle size of 20 μm and the mass fraction of PBO chopped fibers with nickel coating was 2 wt%. Alumina ball milling balls were added, and the ball-to-material ratio was 2:1. (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment, the ball milling speed is 100 r / min, and the ball milling time is 8 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) placing the mixed material into a cemented carbide mold and placing it in a spark plasma sintering (SPS) furnace for sintering at a sintering temperature of 450°C, a sintering pressure of 300 MPa, and a heat and pressure holding time of 45 min. After sintering, demolding is performed to obtain a PBO chopped fiber reinforced aluminum matrix composite body with a nickel-plated surface; (8) placing the surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material blank into a vacuum atmosphere sintering furnace for high-temperature annealing treatment, the annealing temperature is 300°C, the annealing holding time is 4 hours, and after the annealing is completed, the blank is cooled to room temperature with the furnace to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material; A PBO chopped fiber reinforced aluminum-based composite material prepared in this embodiment has a density of 99.3%, a tensile yield strength of 265 MPa, a tensile strength of 310 MPa, a flexural strength of 420 MPa, and an elongation after fracture of 13.5%, and has good comprehensive mechanical properties.

[0017] Example 2 In this embodiment, a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the following method: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) into concentrated sulfuric acid for roughening treatment, wherein the length of the PBO chopped fibers is 6 mm, the concentration of the concentrated sulfuric acid is 90%, and the immersion time is 10 s to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.08mol / L, the concentration of sodium citrate is 0.10mol / L, the concentration of sodium hypophosphite is 0.05mol / L, the concentration of sodium pyrophosphate is 0.10mol / L, the pH regulator is KOH, and the pH value of the nickel plating solution is 13; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 45 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 90°C, the nickel plating reaction time is 150 min, and after the nickel plating is completed, the fibers are rinsed with deionized water for 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; (5) PBO chopped fibers with nickel coating and aluminum powder were mixed and placed in a ball mill, wherein the aluminum powder had a particle size of 200 μm and the mass fraction of PBO chopped fibers with nickel coating was 10 wt%. Alumina ball milling balls were added, and the ball-to-material ratio was 8:1. (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment. The ball milling speed is 500 r / min and the ball milling time is 2 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) The mixed material is placed in a cemented carbide mold and placed in a spark plasma sintering (SPS) furnace for sintering. The sintering temperature is 600°C, the sintering pressure is 100 MPa, and the heat preservation and pressure holding time is 10 min. After the sintering is completed, the mold is demolded to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite body; (8) placing the nickel-plated PBO chopped fiber reinforced aluminum matrix composite body in a vacuum atmosphere sintering furnace for high temperature annealing treatment, the annealing temperature is 500°C, the annealing holding time is 1 hour, and after the annealing is completed, the furnace is cooled to room temperature to obtain a nickel-plated PBO chopped fiber reinforced aluminum matrix composite material; A PBO chopped fiber reinforced aluminum-based composite material prepared in this embodiment has a density of 99.3%, a tensile yield strength of 270 MPa, a tensile strength of 320 MPa, a flexural strength of 430 MPa, and an elongation after fracture of 13.8%, and has good comprehensive mechanical properties.

[0018] Example 3 In this embodiment, a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the following method: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) into concentrated sulfuric acid for roughening treatment, wherein the length of the PBO chopped fibers is 3 mm, the concentration of the concentrated sulfuric acid is 70%, and the immersion time is 20 s to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.03mol / L, the concentration of sodium citrate is 0.02mol / L, the concentration of sodium hypophosphite is 0.10mol / L, the concentration of sodium pyrophosphate is 0.15mol / L, the pH regulator is KOH, and the pH value of the nickel plating solution is 10; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 15 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 60°C, the nickel plating reaction time is 80 min, and after the nickel plating is completed, the fibers are rinsed with deionized water 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; (5) PBO chopped fibers with nickel coating and aluminum powder were mixed and placed in a ball mill, wherein the aluminum powder had a particle size of 100 μm and the mass fraction of PBO chopped fibers with nickel coating was 7 wt%. Alumina ball milling balls were added, and the ball-to-material ratio was 3:1. (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment. The ball milling speed is 200 r / min and the ball milling time is 3 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) The mixed material is placed in a cemented carbide mold and placed in a spark plasma sintering (SPS) furnace for sintering. The sintering temperature is 475°C, the sintering pressure is 150 MPa, and the heat preservation and pressure holding time is 15 min. After the sintering is completed, the mold is demolded to obtain a PBO chopped fiber reinforced aluminum matrix composite body with a nickel-plated surface; (8) placing the surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material blank into a vacuum atmosphere sintering furnace for high-temperature annealing treatment, the annealing temperature is 350°C, the annealing holding time is 2 hours, and after the annealing is completed, the furnace is cooled to room temperature to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material; A PBO chopped fiber reinforced aluminum-based composite material prepared in this embodiment has a density of 99.1%, a tensile yield strength of 260 MPa, a tensile strength of 305 MPa, a flexural strength of 425 MPa, and an elongation after fracture of 13.0%, and has good comprehensive mechanical properties.

[0019] Example 4 In this embodiment, a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the following method: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) into concentrated sulfuric acid for roughening treatment, wherein the length of the PBO chopped fibers is 4 mm, the concentration of the concentrated sulfuric acid is 80%, and the immersion time is 40 seconds to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.06mol / L, the concentration of sodium citrate is 0.05mol / L, the concentration of sodium hypophosphite is 0.16mol / L, the concentration of sodium pyrophosphate is 0.25mol / L, the pH adjuster is KOH, etc., and the pH value of the nickel plating solution is 12; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 30 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 80°C, the nickel plating reaction time is 120 min, and after the nickel plating is completed, the fibers are rinsed with deionized water 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; (5) PBO chopped fibers with nickel coating and aluminum powder were mixed and placed in a ball mill, wherein the aluminum powder had a particle size of 120 μm and the mass fraction of PBO chopped fibers with nickel coating was 3 wt%. Alumina ball milling balls were added, and the ball-to-material ratio was 6:1. (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment. The ball milling speed is 400 r / min and the ball milling time is 5 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) The mixed material is placed in a cemented carbide mold and placed in a spark plasma sintering (SPS) furnace for sintering. The sintering temperature is 575°C, the sintering pressure is 250 MPa, and the heat preservation and pressure holding time is 30 min. After the sintering is completed, the mold is demolded to obtain a PBO chopped fiber reinforced aluminum matrix composite body with a nickel-plated surface; (8) placing the nickel-plated PBO chopped fiber reinforced aluminum matrix composite body in a vacuum atmosphere sintering furnace for high temperature annealing treatment, the annealing temperature is 450°C, the annealing holding time is 3 hours, and after the annealing is completed, the furnace is cooled to room temperature to obtain a nickel-plated PBO chopped fiber reinforced aluminum matrix composite material; A PBO chopped fiber reinforced aluminum-based composite material prepared in this embodiment has a density of 99.5%, a tensile yield strength of 255 MPa, a tensile strength of 295 MPa, a flexural strength of 420 MPa, and an elongation after fracture of 12.5%, and has good comprehensive mechanical properties.

[0020] Example 5 In this embodiment, a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite material is prepared by the following method: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) into concentrated sulfuric acid for roughening treatment, wherein the length of the PBO chopped fibers is 5 mm, the concentration of the concentrated sulfuric acid is 90%, and the immersion time is 30 seconds to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.06mol / L, the concentration of sodium citrate is 0.06mol / L, the concentration of sodium hypophosphite is 0.15mol / L, the concentration of sodium pyrophosphate is 0.20mol / L, the pH regulator is KOH, and the pH value of the nickel plating solution is 11; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 25 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 70°C, the nickel plating reaction time is 100 min, and after the nickel plating is completed, the fibers are rinsed with deionized water for 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; (5) PBO chopped fibers with nickel coating and aluminum powder were mixed and placed in a ball mill, wherein the aluminum powder had a particle size of 80 μm and the mass fraction of PBO chopped fibers with nickel coating was 5 wt%. Alumina ball milling balls were added, and the ball-to-material ratio was 4:1. (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment. The ball milling speed is 200 r / min and the ball milling time is 4 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) The mixed material is placed in a cemented carbide mold and placed in a spark plasma sintering (SPS) furnace for sintering. The sintering temperature is 550°C, the sintering pressure is 200 MPa, and the heat preservation and pressure holding time is 20 min. After the sintering is completed, the mold is demolded to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite body; (8) placing the surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material blank into a vacuum atmosphere sintering furnace for high-temperature annealing treatment, the annealing temperature is 400°C, the annealing holding time is 2 hours, and after the annealing is completed, the blank is cooled to room temperature with the furnace to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material; A PBO chopped fiber reinforced aluminum-based composite material prepared in this embodiment has a density of 99.0%, a tensile yield strength of 263 MPa, a tensile strength of 314 MPa, a flexural strength of 419 MPa, and an elongation after fracture of 13.3%, and has good comprehensive mechanical properties.

[0021] Comparative Example 1 The difference from Example 1 is: The PBO chopped fibers are not subjected to nickel plating. The PBO chopped fibers are dispersed, dried, and then evenly mixed with aluminum powder. A PBO chopped fiber reinforced aluminum matrix composite material is prepared by a spark plasma sintering process.

[0022] A PBO chopped fiber reinforced aluminum-based composite material prepared in this comparative example has a density of 99.0%, a tensile yield strength of 205 MPa, a tensile strength of 255 MPa, a flexural strength of 350 MPa, and an elongation after fracture of 12.0%.

[0023] By comparing Example 1 with the comparative example, it can be seen that, under the premise of the same fiber reinforcement content, ball milling process, sintering process and annealing process, since the surface of the PBO chopped fibers is not nickel-plated, during the sintering preparation process, the interface between the fibers and the aluminum matrix does not react to form NiAl intermetallic compounds, and the interface bonding performance is poor, resulting in a significant decrease in the yield strength, tensile strength and flexural strength of the composite material.

[0024] Comparative Example 2 The difference from Example 2 is: (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent at a concentration of 45 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency being 10-20 kHz, the nickel plating temperature being room temperature (25°C), and the nickel plating reaction time being 150 min. After the nickel plating is completed, the fibers are rinsed with deionized water for 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; A PBO chopped fiber reinforced aluminum-based composite material prepared in this comparative example has a density of 99.0%, a tensile yield strength of 225 MPa, a tensile strength of 260 MPa, a flexural strength of 380 MPa, and an elongation after fracture of 14.0%.

[0025] By comparing Example 2 with this comparative example, it can be seen that under the premise of the same nickel plating solution composition ratio, nickel plating reaction time, fiber reinforcement content, ball milling process, sintering process and annealing process, due to the low nickel plating reaction temperature, the degree of reaction between the reactants during the nickel plating process is low, the thickness and density of the nickel plating layer on the surface of the PBO fiber are poor, and thus the yield strength, tensile strength and flexural strength of the composite material are significantly reduced.

[0026] Comparative Example 3 The difference from Example 2 is: (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of which is 45 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency is 10-20 kHz, the nickel plating temperature is 90°C, the nickel plating reaction time is 300 min, and after the nickel plating is completed, the fibers are rinsed with deionized water for 7-10 times and dried at 70-120°C to obtain PBO chopped fibers with surface nickel plating; A PBO chopped fiber reinforced aluminum-based composite material prepared in this comparative example has a density of 99.0%, a tensile yield strength of 235 MPa, a tensile strength of 270 MPa, a flexural strength of 375 MPa, and an elongation after fracture of 11.0%.

[0027] By comparing Example 2 with the comparative example, it can be seen that under the premise of the same nickel plating solution composition ratio, nickel plating reaction temperature, fiber reinforcement content, ball milling process, sintering process and annealing process, due to the long nickel plating reaction time, the thickness of the nickel plating layer on the surface of the PBO chopped fiber is uneven after the nickel plating treatment, resulting in a significant decrease in the yield strength, tensile strength, flexural strength and elongation after break of the composite material.

[0028] Comparative Example 4 The difference from Example 4 is: (7) The mixed material is placed in a cemented carbide mold and placed in a spark plasma sintering (SPS) furnace for sintering. The sintering temperature is 275°C, the sintering pressure is 250 MPa, and the heat preservation and pressure holding time is 30 min. After the sintering is completed, the mold is demolded to obtain a PBO chopped fiber reinforced aluminum matrix composite body with a nickel-plated surface; A PBO chopped fiber reinforced aluminum-based composite material prepared in this comparative example has a density of 91.5%, a tensile yield strength of 120 MPa, a tensile strength of 145 MPa, a flexural strength of 190 MPa, and an elongation after fracture of 9.5%.

[0029] By comparing Example 4 with this comparative example, it can be seen that under the premise that the nickel plating process, fiber reinforcement content, ball milling process, sintering pressure, insulation and pressure holding time and annealing temperature are the same, when the sintering temperature is too low, the aluminum matrix and the surface nickel-plated PBO chopped fibers cannot fully react, resulting in the inability to sinter the composite material to be dense, and its yield strength, tensile strength, flexural strength and elongation after fracture are significantly reduced, and good comprehensive mechanical properties cannot be achieved.

[0030] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material, characterized in that: The method steps include: (1) placing the PBO chopped fibers in an ultrasonic dispersion device, adding anhydrous ethanol thereto, and performing ultrasonic dispersion treatment. After the dispersion is completed, filtering out the fibers and drying them; (2) immersing the PBO chopped fibers treated in step (1) in concentrated sulfuric acid for roughening treatment, wherein the concentration of the concentrated sulfuric acid is 60-90% and the immersion time is 10-40 seconds. After immersion, the fibers are rinsed with deionized water to obtain PBO chopped fibers to be plated; (3) Prepare chemical nickel plating solution, the solvent used includes: nickel sulfate hexahydrate, sodium citrate, sodium hypophosphite, sodium pyrophosphate, pH regulator and deionized water, among which Ni 2+ The concentration of is 0.02~0.08mol / L, the concentration of sodium citrate is 0.01~0.10 mol / L, the concentration of sodium hypophosphite is 0.05~0.20mol / L, the concentration of sodium pyrophosphate is 0.10~0.30mol / L, the pH regulator is NaOH, KOH or ammonia water, and the pH value of the nickel plating solution is 9~13; (4) immersing the PBO chopped fibers in a nickel plating solution, adding iron as a reaction medium, adding sodium hypophosphite as a reducing agent, the concentration of sodium hypophosphite being 10-45 g / L, and performing chemical nickel plating under ultrasonic stirring, the ultrasonic frequency being 10-20 kHz, the nickel plating temperature being 50-90° C., the nickel plating reaction time being 60-150 min, and after the nickel plating is completed, rinsing the fibers with deionized water for 7-10 times and drying at 70-120° C. to obtain PBO chopped fibers with surface nickel plating; (5) Mixing the nickel-plated PBO chopped fibers and aluminum powder into a ball mill, wherein the mass fraction of the nickel-plated PBO chopped fibers is 2-10 wt%, and adding alumina ball milling balls, wherein the ball-to-material ratio is 2-8:1; (6) The ball mill jar is fixed in a three-dimensional planetary vibration ball mill for ball milling and mixing treatment, the ball milling speed is 100-500 r / min, and the ball milling time is 2-8 h to obtain a uniformly mixed surface nickel-plated PBO chopped fiber / aluminum powder mixture; (7) placing the mixed material into a cemented carbide mold and placing it in a spark plasma sintering (SPS) furnace for sintering treatment, the sintering temperature is 450-600°C, the sintering pressure is 100-300 MPa, and the heat preservation and pressure holding time is 10-45 min. After the sintering is completed, demolding is performed to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum matrix composite body; (8) The surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material blank is placed in a vacuum atmosphere sintering furnace for high-temperature annealing treatment. The annealing temperature is 300-500°C and the annealing insulation time is 1-4 hours. After the annealing is completed, it is cooled to room temperature with the furnace to obtain a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material.

2. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (2), the length of the PBO chopped fibers is 1-6 mm, the concentration of concentrated sulfuric acid used for the roughening treatment is 70-80%, and the immersion time is 20-40 s.

3. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (3), Ni in the nickel plating solution 2+ The concentration of is 0.03~0.06mol / L, the concentration of sodium citrate is 0.02~0.05mol / L, the concentration of sodium hypophosphite is 0.10~0.16mol / L, the concentration of sodium pyrophosphate is 0.15~0.25mol / L, and the pH value of the nickel plating solution is 10~12.

4. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (4), the concentration of sodium hypophosphite is 15-30 g / L, the nickel plating temperature is 60-80° C., and the nickel plating reaction time is 80-120 min.

5. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (5), the particle size of the aluminum powder is 20-200 μm, the mass fraction of the nickel-plated PBO chopped fibers is 3-7 wt %, and the ball-to-material ratio is 3-6:

1.

6. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (6), the ball milling speed is 200-400 r / min, and the ball milling time is 3-5 h.

7. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (7), the spark plasma sintering temperature is 475-575° C., the sintering pressure is 150-250 MPa, and the heat and pressure holding time is 15-30 min.

8. The method for preparing a surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material according to claim 1, characterized in that: In the step (8), the high temperature annealing temperature is 350-450° C., and the annealing holding time is 2-3 hours.

9. A surface nickel-plated PBO chopped fiber reinforced aluminum-based composite material prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Aluminum oxide short fiber reinforced nickel based composite for automobile brake disc patch and preparation method of aluminum oxide short fiber reinforced nickel based composite

    CN106244955A

  • Preparation method of carbon fiber reinforced aluminum matrix composite

    CN110484840A

  • Preparation method of modified carbon fiber and zirconium carbide reinforced aluminum-based composite material

    CN112501523A

  • Preparation method of chopped fiber reinforced ceramic matrix composite material

    CN113999012A

  • Graphene reinforced Ti / Al3Ti micro-laminated composite material and preparation method thereof

    CN117721341A